Effects of particle size and content of RDX on burning stability of RDX-based propellants - Bin-bin Wang; Xin Liao; Luigi T. DeLuca; Wei-dong He (Defence Technology, 2022)
Particle size and content of RDX are the two main factors that affect the burning stability of RDX-based propellants. However, these effects and the corresponding mechanisms are still controversial. In this work, we investigated the physicochemical processes during burning and the corresponding mechanisms through the technologies of structure compactness analysis on the base of voidage measurement and theoretical interfacial area estimation, apparent burning rate measurement using closed vessel (CV) and extinguished burning surface characterization relying on interrupted closed vessel (ICV) and scanning electron microscope (SEM). The results indicate that the voidage increased with the increase of RDX content and particle size due to the increasing interfacial area and increasing interface gap size, respectively. The apparent burning rate increased with the increase of RDX particle size because of the decreasing RDX specific surface area on the burning surface, which could decrease the heat absorbing rates of the melting and evaporation processes of RDX in the condensed phase. Similarly, the apparent burning rate decreased with the increase of RDX content at pressures lower than around 55 MPa due to the increasing RDX specific surface area. Whereas, an opposite trend could be observed at pressures higher than around 55 MPa, which was attributed to the increasing heat feedback from the gas phase as the result of the increasing propellant energy. For propellants containing very coarse RDX particles, such as 97.8 and 199.4 μm average size, the apparent burning rate increased stably with a flat extinguished surface at pressures lower than around 30 MPa, while increased sharply above around 30 MPa with the extinguished surface becoming more and more rugged as the pressure increased. In addition, the turning degree of u-p curve increased with the increase of coarse RDX content and particle size, and could be reduced by improving the structure compactness.